Pemberian minuman kombinasi maltodekstrin dan vitamin C terhadap mood negatif dan VO2 maks atlet sepak bola - Yuni Afriani; Noor Rochman Hadjam; Arta Farmawati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Stress during the match can influence the change of mood and performance of athletes. Physical exercise can improve the ability of physiologically and psychologically, but lead to fatigue, dehydration and hypoglycemia. Maltodextrin has a lower osmolarity to improve emotional and performance. Vitamin C as a cofactor of neurotransmitters can support the performance of athletes.Objective: This study aimed to determine the effectiveness of a combination drinks of maltodextrin and vitamin C on mood and the correlation with VO2 max of football athletes.Method: This research is a quasi experimental with same subject design. The subjects were 14 University state of Yogyakarta football athlete. Subjects received a drink of 15% maltodextrin and 250 mg of vitamin C in 300 ml given 30 minutes before and 5 minutes after the performance test using yo-yo intermittent test continued by physical exercise. Measurement of mood would be done in 3 times; before cardiorespiratory test, 5 minutes after physical exercise, and 15 minutes after drink.Results: There are significant changes after consuming a combination of maltodextrin and vitamin C on the confusion (p<0.05), while components of anger, fatigue, depression, tension and vigor (p>0.05). There are significant changes after consuming plain water on fatigue and tension (p<0.05), while anger, confusion, depression, and vigor (p>0.05). There are no significant differences in every components of mood between two treatments. There is a correlation between anger and confusion with cardiorespiratory after consuming a combination of maltodextrin and vitamin C.Conclusion: Maltodextrin and vitamin C has the potential effect to improve the mood condition and have a correlation with VO2 Max improvement in football athletes.